Expectancy Disconfirmation Theory: A Systematic Literature Review of Satisfaction & Behavioral Intentions - Sumantra Yasa, I Kadek Java; Iqbal, Mohammad; Pangestuti, Edriana (FIA UB, 2026)
Tourist satisfaction is known as one of the main antecedents affecting revisit intention, destination loyalty and word-of-mouth behavior. According to Expectancy Disconfirmation Theory (EDT), satisfaction results when pre-visit expectations are compared with actual experiences. This paper entails an SLR of the applications of EDT in tourism between 1993 and 2025 based on 160 articles indexed by Scopus and WoS, selecting ten for a systematic review. The SLR Methods involving four stages: (1) data base searches from Scopus and Web of Science using targeted EDT-related keywords, (2) screening based on peer-review status and journal quality, (3) eligibility assessment, (4) synthesis using qualitative content analysis. The results strongly highlight the applicability of EDT with regard to heritage tourism, wellness tourism and technology-oriented travel. The empirical findings indicate that effective disconfirmation improves satisfaction and revisit intentions, whereas ineffectual disconfirmation diminishes loyalty. Recent research also emphasizes that it is important to incorporate EDT with other related constructs such as perceived value, memorable tourism experiences and emotional engagement for a more comprehensive explanation of tourist behavior. Implications: This paper adds to theory by providing an overview of the evolution of EDT and also in practice by providing evidence on expectation management and service quality improvement.